Immunization‐related complex regional pain syndrome: A systematic review of case reports - William K. Copenhaver; Brandon J. Goodwin; Alexa Simonetti; Kunal P. Shah; Nicholas J. Averell; David F. Lo; Richard T. Jermyn (PCN Reports)
Abstract Aim Vaccines have been shown to have the highest efficacy in preventing infectious diseases through their ability to induce immunological memory against pathogens. An adverse reaction to a vaccine is an unexpected medical occurrence following immunization. Complex regional pain syndrome (CRPS) is a disease that has undergone much controversy regarding its onset post‐vaccination. This systematic review aims to evaluate cases of CRPS post‐vaccination to better understand the manifestation of the disease and its potential association with vaccines. Methods A systematic review of case reports was conducted employing the PRISMA 2020 guidelines. Outcomes of interest include type of vaccination, patient age, patient sex, time to symptom onset, and medical history including but not limited to previous autoimmune diseases, psychological illness, physical tissue trauma, and neurological disease. Results Initial querying of the five databases yielded 404 articles. Following a thorough review of articles, only 14 remained, comprising 18 cases. Studies included cases of CRPS development following tetanus, hepatitis B, hepatitis A, rubella, influenza, tetanus–diphtheria, human papillomavirus, and COVID‐19 vaccine administration. Conclusion The limitations of evidence used in this study highlight the need for a greater output of higher‐level evidence in the form of controlled trials and retrospective studies to help further elucidate the connection between vaccine use and the development of CRPS in patients. Currently, vaccines continue to be safe for global public use.